Determinants of Ethical Identity Disclosure in Islamic Banks: Empirical Evidence in Indonesian Islamic Banks - Erlinda Nur Khasanah; Wia Rizqi Amalia (UIN Siber Syekh Nurjati Cirebon, 2021)
This study aimed to determined factors influencing the disclosure of ethical identity. The data used in this study was secondary data taken from Islamic Banks annual report from 2013-2016. Total sample consisted of 44 samples. To test the hypothesis, this study used multiple regression analysis. This study found that the disclosure of Islamic Bank’s ethical identity in Indonesia were considered quite low. The size of Audit Committee significantly influenced the disclosure of ethical identity, while other factors; the size of Board of Directors were not significant, and both the Board of Commissioners and the Shari’ahh Supervisory Board were found negatively significant to the disclosure of ethical identity.